Environmental plasticity of short-stemmed winter bread wheat (Triticum aestivum L.) cultivars and resistance to yellow leaf blotch (Pyrenophora tritici-repentis (Died.) Drechsler) and brown (leaf) rust (Puccinia recondita f. sp. tritici Rob. et Desm.) - Yarosh, A.V.; Kucherenko, Ye.Yu.; Riabchun, V.K.; Kuzmyshyna , N.V.; Solonechna, O.V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
In the context of variability of common pathogens of foliar diseases of winter bread wheat, evolvement of virulent and aggressive races, and periodic droughts, which with climate changes increasingly occur in the territory of Ukraine, prerequisites for in-depth research into adaptability of plant varieties and selection of the best gene pool for breeding arise. The paper presents results on the environmental plasticity of short-stemmed winter bread wheat cultivars, which were differentiated by resistance to yellow leaf blotch and brown (leaf) rust. New sources of high and stable group resistance to pathogenes of these diseases were identified: cv. ’Versiia odeska’ (UKR) and cv. ’Mescal’ (FRA). By genotypic effect (εi) and regression coefficient (Ri) for yield, the following genotypes showing the highest genetic potential for adaptability (sum of ranks = 2) to stressful conditions of cultivation in the eastern forest-steppe of Ukraine and yielding by 16% more than the check cultivar were identified among the short-stemmed cultivars under investigation: cv. ’Pokrovska’ (εi = 1.92; Ri = 0.60) (UKR), cv. ’Versiia odeska’ (εi = 1.21; Ri = 0.77) (UKR), cv. ’MIP Vidznaka’ (εi = 1.05; Ri = 0.82) (UKR), cv. ’Mescal’ (εi = 0.98; Ri = 0.65) (FRA), and cv. ’SY Wolf’ (εi = 0.94; Ri = 0.69) (USA). It was found that the genotypic effect for yield ranged from -1.71 to 1.92 in the short-stemmed cultivars, and the regression coefficient - from 0.60 to 1.45, which largely affected the environmental plasticity: the sum of ranks for this parameter varied from 2 to 6. The percentage of accessions with high genotypic effects was 33.3%; the percentage of accessions with consistently stable yields was 41.7%. It was revealed that in short-stemmed winter bread wheat, resistance to brown rust and yellow leaf blotch was significantly negatively correlated with the sum of ranks of the genotypic effect and regression coefficient for yield (r = -0.65, P < 0.01 and r = - 0.58, P<0.01, respectively). The selected sources of high group resistance to Pyrenophora tritici-repentis (Died.) Drechsler) and brown (leaf) rust (Puccinia recondita f. sp. tritici Rob. et Desm., with high yield potential and stability, are valuable starting materials for the breeding of new, highly promising winter bread wheat cultivars, which will be adaptable to stressful conditions of cultivation in the eastern forest-steppe of Ukraine.